LEARNING STYLE OF MEDICAL STUDENTS AND ITS CORRELATION WITH PREFERRED TEACHING METHODOLOGIES AND ACADEMIC ACHIEVEMENT - Bhalli, Muhammad Asif; Khan, Ishtiaq Ali; Sattar, Abdul (Journal of Ayub Medical College Abbottabad, 2016)
Background: Researchers have categorized the learning styles in many ways. Kolb proposed a classification of learner’s styles as convergers, divergers, assimilators and accommodators. Honey and Mumford simplified learning styles as activists, reflectors, theorists and pragmatists. Neil Fleming’s VARK model (Visual, Auditory, Read/write and Kinesthetic) is also popular. This study was carried out to determine the frequency of learning styles (Honey and Mumford) of medical students and its correlation with preferred teaching methodologies and academic achievements. Methods: A total of 77 medical students of 4th year MBBS were selected through non-probability convenient sampling for this study. Honey and Mumford’s learning style questionnaire, and a 2nd questionnaire to know their preference for different teaching methodologies were distributed to the students. Learning styles were identified and correlated with preferred teaching methodologies and academic achievements by Chi-square test. Results: Mean age of the medical students was 22.75±1.05 years. Twenty one (27.3%) participants were males and 56 (72.7%) females. By learning styles, 7 (9.1%) medical students were activists, 36 (46.8%) reflectors, 13 (16.9%) theorists and 21 (27.3%) were pragmatists. Out of 77 students, 22 preferred interactive lectures; 16, small group discussion; 20 problem based learning, 10 preferred demonstration on models. Only 01 students preferred one-way lecture as the best teaching methodology. No significant correlation was found between learning styles and preferred teaching methodologies and learning styles and academic scores. Conclusion: Most of the medical students had reflector (46.8%) and pragmatist (27.3%) learning styles. Majority preferred interactive lectures (28.57%) and problem based learning (25.98%) as teaching methodologies. Aligning our instructional strategies with learning styles of the medical students will improve learning and academic performance.